A Relationship between Emotional Regulation and Peace of Mind amongTeachers and HeadTeachers in Elementary Schools,Pakistan:A Public and Private Sector Comparison (Journal of Asian Development Studies, 2026)
This study examines the relationship between emotional regulation and peace of mind among teachers and head teachers in elementary schools in Rawalpindi, Pakistan. The study investigates whether there are significant differences between public and private sector schools. The OECD framework of the Big Five model explained the importance of emotional regulation, which comprises stress resistance, emotional control and optimism. The concept is conceptualised as the independent variable, whereas peace of mind serves as the dependent variable reflecting psychological wellbeing. A quantitative, cross-sectional comparative study was designed. The sample consists of 400 participants (160 male and 240 female), teachers and head teachers from public (84) and private (316) schools in Rawalpindi, Pakistan. Skills were assessed on 6 Likert scales ranging from 'almost never' to 'expert level'. Later, Pearson's correlation and independent-samples t-tests were used for analysis. The research findings indicated that there is a statistically significant positive relationship between emotional regulation and peace of mind (r = [ 0.62], p